Relationship Between Anxiety, Dental Fear of Parents and Collaboration of Children to Dental Treatment - Munayco Pantoja DDS, Evelyn R.; Mattos-Vela DDS, MSc, PhD, Manuel A.; Torres Ramos DDS, MSc, PhD, Gilmer; Blanco Victorio DDS, MSc, Daniel J. (Odovtos - International Journal of Dental Sciences, 2018)
In the clinical history of a child, it is not taken into account any scale that evaluates the anxiety and fear experienced during dental treatment. This would help to define the way to approach the patient and perform a successful treatment. The objective of this study was to determine the relationship between anxiety, dental fear and collaboration of parents and children towards dental treatment. A descriptive and transversal study was carried out. The study’s sample was collected from 177 children of both sexes from 3 to 6-year-old, who visited a health institute for a dental appointment, and also their respective parents. A data collection form was prepared for each patient, which included four evaluation scales: the dental fear questionnaire, the Corah anxiety scale, the Children’s Fear Scale and the Venham graphic test. At the end of the treatment, the child's behavior was evaluated using the Frankl scale. In regard to fear, parents presented little or no (55.9%) and children, under fear (87.6%) in a greater percentage. In reference to anxiety, parents presented low anxiety (57%); children, in their majority, were not anxious (64.4%), and their behavior was positive (71.2%). As a result, anxiety caused by the dental treatment in children and parents is not related; nonetheless, fear is. In addition, there is no relationship between anxiety and fear that parents may experience with regard to the child's collaboration. However, the child's collaboration is related to the fear and anxiety that they may experience during dental treatment.